Adaptation of urine source separation in tropical cities : process optimization and odor mitigation - Zhang, Jiefeng (2013)
Source-separating urine from other domestic wastewaters promotes a more sustainable municipal wastewater treatment system. This study investigated the feasibility and potential issues of applying a urine source-separation system in tropical urban settings. The results showed that source-separated urine underwent rapid urea-hydrolysis (ureolysis) at temperatures between 34–40oC, stale/fresh urine ratios greater than 40%, and/or with slight fecal cross-contamination. Undiluted (or low-diluted) urine favored ureolysis; this can be monitored by measuring conductivity as a reliable and efficient indicator. The optimized parameters demonstrated that an effective urine source-separation system is achievable in tropical urban areas. On the other hand, the initial release of CO2and NH3led to an elevated pressure in the headspace of the collection reservoir, which then dropped to a negative value, primarily due to oxygen depletion by the microbial activity in the gradually alkalized urine. Another potential odor source during the ureolysis process was derived from the high production of volatile fatty acids (VFA), which were mainly acetic, propanoic, and butyric acids. Health concerns related to odor issues might limit the application of source separation systems in urban areas; it is therefore vital to systematically monitor and control the odor emissions from a source separation system. As such, an enhanced ureolysis process can attenuate the odor emissions.